2011
DOI: 10.1002/jrs.3019
|View full text |Cite
|
Sign up to set email alerts
|

Raman and surface‐enhanced Raman scattering in the study of human rotator cuff tissues after shock wave treatment

Abstract: Important improvements of diseases of the rotator cuff supraspinatus tendons are seen after shock wave (SW) treatment. Neo-angiogenesis stimulation and hypercellularization result from short periods of treatment. The present work is an attempt to provide a first approach to these bioprocesses, most likely associated with structural aspects resulting from biochemical changes brought about by the SW. Immunohistochemical data indicate that collagen areas in the tissues are influenced the most by the SW. Presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
3
16
0
1
Order By: Relevance
“…Carcamo and co‐workers used Raman and SERS in the study of human rotator cuff tissues after shock wave treatment. It was found that the main differences between different tissue samples could be correlated with the conformation of collagen . Chiu et al .…”
Section: Biosciencesmentioning
confidence: 99%
“…Carcamo and co‐workers used Raman and SERS in the study of human rotator cuff tissues after shock wave treatment. It was found that the main differences between different tissue samples could be correlated with the conformation of collagen . Chiu et al .…”
Section: Biosciencesmentioning
confidence: 99%
“…8). A partir de trabajos previos en el análisis vibracional Raman sobre compuestos orgánicos y sistemas biológicos (Cárcamo et al 2012a(Cárcamo et al , 2012b, así como de datos publicados (Frost et al 2008;Vandenabeele et al 2000), podemos proponer la presencia de oxalatos y material proteico en la mezcla pictórica. Como se muestra en la línea superior, la existencia de oxalatos puede ser inferida por la observación de las bandas ubicadas a 1465 y 1497 cm -1 , mientras que en la línea inferior podemos atribuir las bandas a1665, 1526 y 1292 cm -1 a los modos de vibración amida i, amida ii y amida iii, respectivamente, correspondientes a la estructura secundaria de proteínas.…”
Section: Resultsunclassified
“…Strong Raman signals from amide I (1664 cm À 1 ), Pro and Hyp (1562 cm À 1 ), amide III (1230 cm À 1 ), and ʋ(C-C) in Pro and Hyp rings (810 cm À 1 ) for Col-I fibers on S_3fibAu_NR can be seen in Fig. 6(d-i) and are listed in Table S5 ( Cárcamo et al, 2012;Gullekson et al, 2011;Lee et al, 2010). This confirms that S_3fibAu_NR is the most SERS-active substrate, which likely creates a strong local EM effect between intra-NCs and at the NCs/NR interface.…”
Section: Quality Assessment Of Col-i Fibersmentioning
confidence: 91%
“…From in vitro studies, matrix metalloproteinases (MMPs), including MMP-1, -9, -13, and -14, can effectively degrade native Col-I fibers surrounding a cell surface through the glycine in Col-I fibers (Aimes and Quigley, 1995;Bigg et al, 2007;Fini et al, 1992;Knauper et al, 1997). In addition, the degradation of Col-I, -II, and -III fibers using various temperature-dependent treatments has been investigated (Cárcamo et al, 2012;Jain et al, 2014; Contents lists available at ScienceDirect Su et al, 2014). Methods for analyzing the degradation of Col-I fibers include the enzyme-linked immunosorbent assay and highperformance liquid chromatography (Akhtar et al, 1999;Hudson et al, 2012), which have excellent sensitivity for the detection of specific degraded enzymes in Col-I fibers.…”
Section: Introductionmentioning
confidence: 99%